2014
DOI: 10.3389/fnagi.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Gait disturbances as specific predictive markers of the first fall onset in elderly people: a two-year prospective observational study

Abstract: Falls are common in the elderly, and potentially result in injury and disability. Thus, preventing falls as soon as possible in older adults is a public health priority, yet there is no specific marker that is predictive of the first fall onset. We hypothesized that gait features should be the most relevant variables for predicting the first fall. Clinical baseline characteristics (e.g., gender, cognitive function) were assessed in 259 home-dwelling people aged 66 to 75 that had never fallen. Likewise, global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 88 publications
0
41
0
1
Order By: Relevance
“…Although causes of falls are often multifactorial, the majority of falls occurs during walking and gait analysis may be the best tool to predict the first fall onset [11,12]. Poor gait is indeed one of the main risk factors of falls and an important indicator of general health [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although causes of falls are often multifactorial, the majority of falls occurs during walking and gait analysis may be the best tool to predict the first fall onset [11,12]. Poor gait is indeed one of the main risk factors of falls and an important indicator of general health [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is growing evidence that neurovascular uncoupling contributes to cognitive decline, the role of neurovascular health in gait abnormalities remains elusive. Second, gait dysfunction in older adults is a major cause of functional impairment, contributes to falls, and predicts increased risk of institutionalization and mortality (Mignardot et al 2014;Nakamura et al 1996;Sorond et al 2010;Verghese et al 2009). Third, gait abnormalities were shown to be associated with survival in older adults (Studenski et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Akira et al [71] found that ice immersion, which is a method of reducing muscle spindle function, had a significant impact on the walking velocity of young adult males, suggesting a possible link between muscle spindle function and a decrement in walking ability, a well-accepted falls determinant. Additional related research suggests it is morphological changes of muscle spindles that many environmental hazards exist that increase the proclivity to falling [69,70,72,74] .…”
Section: Resultsmentioning
confidence: 99%